2022
DOI: 10.1002/hbm.26195
|View full text |Cite
|
Sign up to set email alerts
|

The depth of semantic processing modulates cross‐language pattern similarity in Chinese–English bilinguals

Abstract: Previous studies have investigated factors related to the degree of cross‐language overlap in brain activations in bilinguals/multilinguals. However, it is still unclear whether and how the depth of semantic processing (a critical task‐related factor) affects the neural pattern similarity between native and second languages. To address this question, 26 Chinese–English bilinguals were scanned with fMRI while performing a word naming task (i.e., a task with shallow semantic processing) and a semantic judgment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 105 publications
(176 reference statements)
0
2
0
Order By: Relevance
“…The paired sample t-test showed that the L1 was more pro cient than the L2 in listening (t(23) = -8.741, p < .001), speaking (t(23) = -8.108, p < .001), reading (t(23) = -6.409, p < .001) and writing (t(23) = -8.113, p < .001). These results indicate that participants have intermediate pro ciency in their L2 (see also Liu et al, 2022Liu et al, , 2023 for a similar sample). The names of the colors and shapes were monosyllabic pseudowords (e.g., "sa" for yellow, "da" for pentagram).…”
Section: Participantsmentioning
confidence: 64%
“…The paired sample t-test showed that the L1 was more pro cient than the L2 in listening (t(23) = -8.741, p < .001), speaking (t(23) = -8.108, p < .001), reading (t(23) = -6.409, p < .001) and writing (t(23) = -8.113, p < .001). These results indicate that participants have intermediate pro ciency in their L2 (see also Liu et al, 2022Liu et al, , 2023 for a similar sample). The names of the colors and shapes were monosyllabic pseudowords (e.g., "sa" for yellow, "da" for pentagram).…”
Section: Participantsmentioning
confidence: 64%
“…They all came from Beijing and had highly similar second language education backgrounds. All participants were healthy, right-handed and had normal or corrected-to-normal vision ( Yuan et al, 2021 ; Li et al, 2023 ). All participants signed an informed consent form before the experiment, which was approved by the Institutional Review Board of Beijing Normal University.…”
Section: Methodsmentioning
confidence: 99%